Patients with HBV, HCV and HIV antigens medical management rules – hospitalization, surgical procedures, equipment sterilization principles - Szaflik, Jerzy; Bełżecka-Majszyk, Agata (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
The purpose of the study was to present information about clinical treatment of HIV, HBV and HCV infection seropositive patients. We present indications and principles for hospitalization, conventional and surgical treatment and sterilization methods.